(untitled) (International Journal of Environmental Sciences, 2025)
Background: Caspofungin, an echinocandin antifungal, has limited topical application due to poor solubility and skin permeability. To overcome these limitations, a Caspofungin-loaded emulgel was developed, aiming to enhance local drug delivery and improve antifungal efficacy against skin infections. Method:A stable emulgel formulation was developed using Carbopol 940 as the gelling agent and liquid paraffin as the oil phase. Nine batches (F1–F9) were prepared by varying concentrations of Carbopol and paraffin, optimized through a Central Composite Design (CCD). Compatibility between drug and excipients was confirmed using FTIR. Evaluation included pH, viscosity, spreadability, drug content, and in-vitro drug release via Franz diffusion cell. Research:All formulations were physicochemically stable. Batch F7 exhibited the most promising results with 96% drug content and 97.3% drug release. Viscosity and spreadability were within acceptable limits, ensuring ease of application. Statistical analysis showed Carbopol 940 significantly influenced drug content, while liquid paraffin had a major effect on drug release. Response surface and contour plots validated these interactions. Conclusion:The optimized emulgel formulation demonstrated excellent stability, uniform drug distribution, and enhanced in-vitro drug release. Caspofungin emulgel represents a promising topical delivery system for antifungal treatment, combining improved skin permeability and patient compliance.